10 Steps to positive living - Dryden, Windy (Orient Delhi, 2002)
"10 Steps to Positive Living" by Dr. Windy Dryden, published in 2005, offers practical guidance for adopting a more positive and fulfilling life. Drawing from Rational Emotive Behavior Therapy (REBT), a form of Cognitive Behavioral Therapy (CBT), the book presents ten actionable steps to help individuals take control, embrace flexibility, accept reality, and improve relationships. Each step is designed to be followed sequentially or individually, allowing readers to tailor the approach to their personal goals. The book is illustrated with color photographs and diagrams to enhance understanding.